2021
DOI: 10.1016/j.psychsport.2020.101826
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity is positively associated with college students' positive affect regardless of stressful life events during the COVID-19 pandemic

Abstract: The study was designed to determine associations between physical activity (PA) and affect before and during COVID-19 stay-at-home orders and how change in PA predicted change in affect during this time. Before and during COVID-19 stay-at-home orders, college students (n = 107) completed assessments of PA, positive and negative affect, sleep quality, food insecurity, and stressful life events (during stay-at-home order only). Total minutes of PA was positively associated with positive affect before ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
98
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 27 publications
11
98
3
1
Order By: Relevance
“…On the other hand, Sañudo et al ( 2020 ) showed an objective reduction in PA with 67.7% fewer steps per day during the lockdown. In the same line, five studies showed a reduction of light/mild PA (walking) between 32.5 and 365.5% compared to the period prior to confinement (Ács et al, 2020 ; Barkley et al, 2020 ; Gallè et al, 2020 ; Gallo et al, 2020 ; Sañudo et al, 2020 ), three studies found a decrease in moderate PA levels (from 14–59.7%) (Barkley et al, 2020 ; Gallè et al, 2020 ; Sañudo et al, 2020 ) and four studies in moderate-to-vigorous PA (MVPA) (from 3.9–56.6%) (Karuc et al, 2020 ; Maher et al, 2020 ; Sañudo et al, 2020 ; Savage et al, 2020 ). Finally, seven studies also revealed a reduction of high/vigorous PA between 2.9 and 52.8% compared to pre-lockdown (Ács et al, 2020 ; Barkley et al, 2020 ; Gallè et al, 2020 ; Gallo et al, 2020 ; Romero-Blanco et al, 2020 ; Sañudo et al, 2020 ; Alarcón Meza and Hall-López, 2021 ) and two studies showed a decrease of total PA (28.6 and 50%) (Ács et al, 2020 ; Gallè et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Sañudo et al ( 2020 ) showed an objective reduction in PA with 67.7% fewer steps per day during the lockdown. In the same line, five studies showed a reduction of light/mild PA (walking) between 32.5 and 365.5% compared to the period prior to confinement (Ács et al, 2020 ; Barkley et al, 2020 ; Gallè et al, 2020 ; Gallo et al, 2020 ; Sañudo et al, 2020 ), three studies found a decrease in moderate PA levels (from 14–59.7%) (Barkley et al, 2020 ; Gallè et al, 2020 ; Sañudo et al, 2020 ) and four studies in moderate-to-vigorous PA (MVPA) (from 3.9–56.6%) (Karuc et al, 2020 ; Maher et al, 2020 ; Sañudo et al, 2020 ; Savage et al, 2020 ). Finally, seven studies also revealed a reduction of high/vigorous PA between 2.9 and 52.8% compared to pre-lockdown (Ács et al, 2020 ; Barkley et al, 2020 ; Gallè et al, 2020 ; Gallo et al, 2020 ; Romero-Blanco et al, 2020 ; Sañudo et al, 2020 ; Alarcón Meza and Hall-López, 2021 ) and two studies showed a decrease of total PA (28.6 and 50%) (Ács et al, 2020 ; Gallè et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…One thousand one hundred thirty-seven references were identified after search process in four databases, of which 10 (Ács et al, 2020 ; Barkley et al, 2020 ; Gallè et al, 2020 ; Gallo et al, 2020 ; Karuc et al, 2020 ; Maher et al, 2020 ; Romero-Blanco et al, 2020 ; Sañudo et al, 2020 ; Savage et al, 2020 ; Alarcón Meza and Hall-López, 2021 ) met the inclusion criteria. Figure 1 shows the flow chart of the selection process of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, more boys were participating in riding lessons, which is a positive step in a sport that is dominated by females [ 19 ]. Physical activity is directly linked to positive mental health, and decreased loneliness [ 20 ]. During a pandemic, acknowledging the importance of mental health is paramount as feelings of stress, anxiety, fear and sadness are heightened [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, we need data on psychological variables of (amateur and recreational) athletes relevant to different stages of the COVID-19 pandemic (see Samuel et al, 2020 ) to gain insights into the mental states of athletes. In detail, this study aims to expand our knowledge on stress, anxiety, and coping during the lockdown ( di Fronso et al, 2020 , p. 10) and to investigate individuals’ motivation or tendency to become physically (more) active when given the chance ( Brand et al, 2020 ; González-Valero et al, 2020 ; Maher et al, 2020 ) during this very unusual time. Current developments underline the increasing relevance of being prepared for such crises and the need for developing appropriate intervention strategies (i.e., second lockdowns, canceled competitions).…”
Section: Introductionmentioning
confidence: 99%